Formative research in Ethiopia and Bangladesh: Strengthening household survey measures of maternal micronutrient supplementation in low- and middle-income countries - Walton, Shelley; Wood, Ellina; Berhane, Hanna Y.; Workneh, Firehiwot; Ferdaweke, Fiker; Billah, Sk Masum; Lotus, Sharif Uddin; Munos, Melinda; Kim, Sunny S.; Manohar, Swetha; Nguyen, Phuong Hong; Azeem, Syed Shehryar; et al. (Gates Foundation, 2025)
Background As countries transition from iron folic acid (IFA) to multiple micronutrient supplements (MMS) for pregnant women, they need accurate data on who is being reached with these interventions. The aim of our formative research in Ethiopia and Bangladesh was to design updated household survey questions, response options, and visual aids to measure coverage of prenatal micronutrient supplements.